Perception and uses about mammals in México: a literature review - Flores-Santiago, Iván; Baena, Martha L.; A. Delfín-Alfonso, Christian; Silva-Rivera, Evodia; Pérez-Chacón, José Luis (Ethnobiology and Conservation, 2024)
The negative effects of human activity on wildlife populations in ecosystems must be addressed not only from an ecological perspective but also from a social approach. One way is through studying the perception of human communities that have frequent interactions with wildlife. We conducted a systematic literature review to understand Mexican rural and urban communities’ perceptions of wild mammals using web search engines. Of 321 studies found on this topic, only 77 met our criteria and were therefore useful for analysis. We presented data of causes of perception in different states of Mexico where the studies were carried out. We found that positive perception was significantly associated with the use of fauna, mainly in the rural environment, followed by the ecological importance in both urban and rural environments. In negative perception we did not find a significant association between these variables, but we did find a tendency to perceive fauna as dangerous. Mammal species mentioned in the articles reviewed were also classified by size, and their association with negative or positive perception. We found that the species with a positive perception with the highest number of mentions in the literature were the white-tailed deer (Odocoileus virginianus), nine-banded armadillo (Dasypus novemcinctus), raccoon (Procyon lotor), paca (Cuniculus paca) and collared peccary (Dicotyles tajacu). Species with negative perception were the Coyote (Canis latrans), white-nosed coati (Nasua narica), Gray fox (Urocyon cinereoargenteus) and long-tailed weasel (Mustela frenata). In rural environments perception of wild mammals was related to the uses, and in urban areas depends on the information acquired at school. These differences play a fundamental role in forming attitudes and behaviors towards wild mammals. Because perceptions and uses of wildlife can influence conservation efforts, educational programs should highlight the important role of wild mammals within their ecosystems.